Answer:
1.1
Step-by-step explanation:
looked it up
Answer:
x= 120
Step-by-step explanation:
x+60=180
x=180-60
x=120
Answer:
-2.26 lb
Step-by-step explanation:
Let the dog's initial weight be d.
Then, one year later, the dog weighs 3.73 lb less, and thus weighed d - 3.73 lb.
During the next year, the dog gained 1.47 lb, so now weighs d - 3.73 + 1.47 lb, or
d - 2.26 lb. This indicates a total weight loss of 2.26 over these two years.
3.122
The process to getting this comes in many steps. Firstly, you need to find the angles for JLK and MLJ. To find JLK use the arcsin function using the opposite side and the hypotenuse.
Arcsin(Opp/Hype) = JLK
Arcsin(.5) = JLK
30 degrees = JLK
This means MLJ = 31 degrees since they add up to 61 degrees.
Now we need to find the length of LJ, which we can do using the Pythagorean Theorem.
3^2 + JL^2 = 6^2
9 + JL^2 = 36
JL^2 = 27
JL =
![\sqrt{27}](https://tex.z-dn.net/?f=%20%5Csqrt%7B27%7D%20)
Now that we have the angle of MLJ and the length of JL, we can use the tangent function to find MJ.
Tan(angle) = opp/adj
Tan(31) = MJ/
![\sqrt{27}](https://tex.z-dn.net/?f=%20%5Csqrt%7B27%7D%20)
![\sqrt{27}](https://tex.z-dn.net/?f=%20%5Csqrt%7B27%7D%20)
Tan(31) = MJ
3.122 = MJ